Análisis del potencial eólico y solar para la implementación de un sistema híbrido de generación eléctrica en base al uso de energías alternativas en el páramo chalupas, periodo 2015 - Hervas Moreira, Jhonatan Alberto (2015)
This project concerns the analysis of wind-solar, the instruments used for data collection and selection potential of the participants to generate electricity and independent functioning of each of the elements existing elements. The system takes advantage of the wind-solar natural resources and conversion methods shows the mechanical to electrical energy. The system consists of mechanical, electrical, electronic storage and parts, which make up a power generation system. The benefit of this project is customer satisfaction based on the study and proper equipment selection, because in this way can meet the energy needs, and achieved very pleasing way linking the University with the People....